Advances in Tumor Immunology and Immunotherapy - Rosenblatt, Joseph D.; Rosenblatt, Joseph D.; Podack, Eckhard R.; Podack, Eckhard R.; Barber, Glen N.; Barber, Glen N.; Ochoa, Augusto.; Ochoa, Augusto. (Current Cancer Research,, 2014)
This volume explores recent advances in understanding of fundamental immunology  and insights into  the dynamic interactions between tumors and the immune system, that  provide new opportunities  for therapeutic  intervention in cancer.  Chapter topics include evolving paradigms in the innate and adaptive response,   newly appreciated immunosuppressive mechanisms,  and  novel preclinical  strategies for manipulation of the immune system for therapeutic benefit in cancer. In addition, recent successes in the clinic, and emerging opportunities are covered. Future possibilities, such as the use of antibody engineering, fusion proteins,  and the retargeting of immune cells through T-cell receptor engineering are discussed by  leaders in the field,  focusing  on recent clinical experience, promising technologies, and challenges to clinical success.